Sources of judicial attitudes toward criminal sanctioning - Frank, James (American journal of criminal justice, 1987)
Through a 1979 survey of 89 Illinois judges, the present study attempts to assess how various social, political, and occupational factors influence judicial attitudes toward criminal sanctioning. Specifically, our analysis examined the relative impact of background characteristics (e.g. age, community context) versus occupational variables (e.g., years on the bench, former prosecutor and/or defense attorney) on five sanctioning scales: rehabilitation, punishment, capital punishment, punishing white-collar offenders, and the treatment of juvenile delinquents. The analysis revealed that political orientation was the most important variable examined. Political ideology was found to be related to all but one of the sanctioning scales (punishing white-collar offenders). In contrast, the social and occupational variables generally were not significantly related to judicial attitudes on the purposes of sentencing.